2022
DOI: 10.1002/ael2.20067
|View full text |Cite
|
Sign up to set email alerts
|

Soil sampling depth impact on phosphorus yield response prediction in winter wheat

Abstract: Nutrient stratification of no-till managed soil can affect soil test analysis levels of plant-available phosphorus (P). Research has suggested sampling to different depths due to soil acidity, but little work has been conducted to investigate any change to sampling recommendations for immobile nutrients. The objective of this study was to determine the soil sampling depth that had the greatest relationship with yield response to fertilizer-P. The depths sampled in this study were 0-5, 0-10, 0-15, 10-30, 5-10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…The use of isolated deeper soil layers (2-4, 2-8, 2-12, 4-8, 4-12, and 8-12 inches) did not improve the diagnosis of P availability at either site. These results contrast with those obtained by Reed et al (2022) and Bellinaso et al (2021). Bellinaso et al (2021) found that soybean yield was more related to the STP in the 4-8 and 8-12 inches layers than in the 0-4 inches layer.…”
Section: Critical Soil Test Values Of P In Different Soil Layerscontrasting
confidence: 88%
See 2 more Smart Citations
“…The use of isolated deeper soil layers (2-4, 2-8, 2-12, 4-8, 4-12, and 8-12 inches) did not improve the diagnosis of P availability at either site. These results contrast with those obtained by Reed et al (2022) and Bellinaso et al (2021). Bellinaso et al (2021) found that soybean yield was more related to the STP in the 4-8 and 8-12 inches layers than in the 0-4 inches layer.…”
Section: Critical Soil Test Values Of P In Different Soil Layerscontrasting
confidence: 88%
“…In this sense, Bellinaso et al (2021) demonstrated that the STP in the 4-8 and 4-6 inches layers have a better correlation with crop productivity than the 0-4 inches layer. Similarly, Reed et al (2022) found that using the 2-4 and 2-6 inches soil layer provided the highest correlation with P yield response for wheat in Oklahoma, and the depths that did not include the 0-2 inches layer were similar or more correlated to P yield response than depths including the 0-2 inches depth. Thus, the objective of the present study was to evaluate the CSTV of P for corn and soybean in different soil layers in two long-term experiments (37 and 56 years) with increasing rates of phosphate fertilizer in North Carolina.…”
Section: Core Ideasmentioning
confidence: 85%
See 1 more Smart Citation